Lost in narrative? The effect of informative narratives on text comprehension and metacomprehension accuracy. (April 2019) - Golke, Stefanie; Hagen, Romina; Wittwer, Jörg
Abstract: Informative narratives are enriched expository texts that provide to-be-learned conceptual information within a storyline with the aim to foster comprehension. However, research casts doubt on such a benefit for comprehension. Additionally, it is an open question how informative narratives impact metacomprehension accuracy. The results of two experiments ( N 1 = 63 and N 2 = 70 university students) showed that informative narratives were less or not at all beneficial to text comprehension compared with expository texts. Moreover, informative narratives often led to more overestimation of comprehension in terms of predictions, postdictions, and response confidence than expository texts. This seemed to be particularly true, as Experiment 2 revealed, for readers with a lower need for cognition because they were more transported into the storyline of informative narratives. The findings suggest that informative narratives prime the activation of a narrative-specific reading goal and, thus, distract readers from learning and accurately monitoring the to-be-learned conceptual information. Highlights: Informative narratives can decrease text comprehension of conceptual information. Informative narratives can produce stronger overestimations of comprehension. Informative narratives can result in poorer discrimination between responses. Lower need for cognition fosters transportation into informative narratives. Higher transportation into informative narratives enhances overestimations.